Distribution and reproductive biology of the Electric ray Discopyge tschudii Heckel, 1846 in San Matías Gulf, Northern Patagonia, Argentina - Estalles, María Lourdes (2011)
The Electric ray Discopyge tschudii is distributed form southern Brazil to Peru. The main threat to this species is fishing. Discopyge tschudii is noncommercial and individuals caught are discarded on board. The present study analyzes the distribution and the morphological and reproductive characteristics of this ray in San Matías Gulf (SMG). A total of 1087 individuals were analyzed. The species presented an aggregated distribution with the main concentrations in the northern and eastern areas of SMG at depths below 100 m. Males ranged from 9 to 43 cm and females from 11 to 38 cm. The species presented sexual dimorphism. Males were larger and heavier than females and they also matured at larger sizes. Size at 50% of maturity was estimated at 30 cm for males and 21 cm for females. A total of 199 embryos were sampled and the proportion of sexes showed no significant differences from the expected 1:1. The number of embryos per female varied from 1 to 12. The most frequent values were 2 and 5. Length at birth was estimated at 82.17 ± 3.87 mm. According to our findings we hypothesizes that the electric ray D. tschudii completes its reproductive cycle in SMG.